CldU sensitizes BRCA2 reverse-mutated cells to PARP inhibitors - Zouggari, Nawel; Trugenberger, Camilla; Du Bois, Valentine; Wang, Wenwen; Rossetti, Giacomo G.; Halazonetis, Thanos D.; Labidi-Galy, Intidhar (Frontiers in Oncology, 2025)
PARP inhibitors are widely used class of drugs for the treatment of homologous recombination deficient cancers, including BRCA mutated ones. These drugs led to substantial improvement in survival, particularly for patients with BRCA mutated tumors. However, many patients eventually develop resistance to PARP inhibitors, mainly due to BRCA reversion mutations. Overcoming resistance to PARP inhibitors is an unmet medical need. Recently, it has been shown that BRCA-deficient cells are hypersensitive to the thymidine analogue 5-chloro-2’-deoxyuridine (CldU), either alone or in combination with PARP inhibitors. In this study, we show, across multiple BRCA2 mutated cell lines, that CldU sensitizes PARP inhibitor-resistant cells to PARP inhibitors. This synergy was also present in cell lines with BRCA2 reversion mutations and was associated with high levels of DNA damage and arrest in S phase. This effect, which is specific to thymidine analogue CldU, may open new avenues for the treatment of BRCA mutated cancers resistant to PARP inhibitors.